Phylogenetic analysis confirms hepatitis C virus transmission among hemodialysis patients in Kosovo - Xhevat Jakupi; Jana Mlakar; Maja Lunar; Ibrahim Rudhani; Lul Raka; Norma Tavakoli; Mario Poljak (Journal of Infection in Developing Countries)
Introduction: It has recently been demonstrated that there is a very high prevalence of hepatitis C virus (HCV) infection among hemodialysis patients in Kosovo with HCV subtype 1 being the most prevalent subtype. In this study, we further detail the molecular epidemiology of HCV outbreaks occurring in seven dialysis centers in Kosovo.